THE EFFECT OF COMPENSATION AND WORKLOAD TO WORK PERFORMANCE MEDIATED BY JOB SATISFACTION - Ariyantini, Dianita; Maharani, Anita; Wihadanto, Ake (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2025)
This research investigates how compensation, workload, and job satisfaction impact work performance. Adopting a deductive methodology, the study tests seven hypotheses examining the direct effects of compensation and workload on performance, as well as their indirect effects mediated by job satisfaction. Data were gathered from 144 employees at the BRIN Main Inspectorate using questionnaires and subsequently analyzed with Structural Equation Modeling (SEM) through Smart PLS (Partial Least Squares). The results highlight job satisfaction's crucial role in bridging the gap between compensation, workload, and work performance. The study concludes by emphasizing the significance of equitable compensation, manageable workloads, and high job satisfaction for enhancing work performance and achieving organizational objectives, offering practical suggestions for improving organizational effectiveness.